DESIGN OF MARITIME HIGHER EDUCATION INSTITUTE IN SUBANG REGENCY, WEST JAVA WITH A METAPHORIC ARCHITECTURE APPROACH - Hendri Hermawan; Asri Budiarto; Ryan Hidayat (Universitas Indraprasta PGRI, 2023)
Indonesia as a maritime country has potential in the field of maritime affairs and fisheries, but still lacks the number of seafarers. Fulfillment of the quantity can be achieved by providing an education program and improvement of the quality of national maritime education, but the availability of maritime education is still too low, especially in West Java. There are only 7 maritime training institutions that are allowed, so there is potential to plan a Maritime College in West Java, where Subang Regency has the potential. The method used is a literature study, precedent studies, and direct observation related to the title, followed by data analysis including site analysis, user activity analysis, spatial analysis, building analysis related to the basic shape of the building or mass composition, appearance or facade buildings, structures and materials, and then utilities. Furthermore, the design starts with interpreting the basic concept of the idea into a sketch of the shape of the building or mass composition, then it is loaded into a design in the form of shop drawings and perspectives which are visualized in the form of animation or mockups. The purpose of this design is to produce a design concept as a basis for designing and being a solution to the problems. The application metaphor architecture is used to represent and perceive the feelings and the other views of visitors when they see the building, where the building will become a public attraction because it has its characteristics in the design of the building which is inspired by pinisi ship and will become a landmark of an area.